A numerical model for soldering process in silicon solar cells. (15th May 2017) - Nasr Esfahani, Sajedeh; Asghari, Saeed; Rashid-Nadimi, Sahar
Highlights: A finite element model is developed to simulate the soldering process. Temperature and stress distributions during the soldering process are predicted. The effective parameters on temperature and stress distribution are described. Abstract: Solar or Photovoltaic (PV) cells are utilized to convert solar energy into electricity through the photovoltaic effect. Although, Silicon solar cell is one of the most prevalent type of solar cells; manufacturing of this type of solar cells especially soldering copper electrodes to the silicon wafer is very challenging. If the soldering parameters are not selected properly, small cracks will be created in silicon layer, and finally, fracture of the solar cell will happen. The goal of the present study is to develop, for the first time, a finite element model to simulate the soldering process in the fabrication of silicon solar cell in which the soldering system is passing over the solar cell to connect the copper electrode to the silicon wafer. The temperature and thermomechanical stress distributions induced in different layers of the cell are extracted. The effects of several parameters such as soldering power, soldering speed, and the thickness of silicon wafer on the temperature and stress distributions are probed. The results show that the silicon layer is the most critical layer in a silicon solar cell during the soldering process which is susceptible to high thermomechanical stresses. It is shown that increasing the soldering system power and decreasing the soldering system speed lead to increase of thermomechanical stresses induced in the silicon wafer. In addition, using thicker silicon wafer can decrease the thermomechanical stresses generated in this layer.